Management Perceptions of the Impact of Quality of Work Life on Organizational Performance - Agrawal, Amee (Prabandhan: Indian Journal of Management, 2019)
The Government sector provides employment to employees on a large scale. In spite of compensating adequately, it has been found that there are issues in the quality of work life of employees working in PSUs. The research was carried out to investigate quality of work life (QWL) of employees and its impact on organizational performance in the public sector. The research was carried out with the help of cross sectional data collected from 115 employees from a public sector undertaking based in Vadodara in the state of Gujarat. The data was measured with a six dimensional scale adopted from Kanten and Sadullah (2012), which was further validated with CFA and the structural models were tested using SEM . The individual processes were further analyzed with correlation analysis. The results obtained are unique and can be used for better policy formulations in the PSUs.